If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(2x + 1) = 9 Reorder the terms: 7x + -1(1 + 2x) = 9 7x + (1 * -1 + 2x * -1) = 9 7x + (-1 + -2x) = 9 Reorder the terms: -1 + 7x + -2x = 9 Combine like terms: 7x + -2x = 5x -1 + 5x = 9 Solving -1 + 5x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 9 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 9 + 1 5x = 9 + 1 Combine like terms: 9 + 1 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| X/9+3=11 | | (2x+3x)/9=25 | | 1+2a=33 | | 2(3+2)= | | 119-6x=30x-23 | | F-0.5=1.2 | | 3x^2+432=0 | | 0.4x+0.3=-0.1 | | 45=(20x) | | x+1.3=5.7 | | 144y^2+25=0 | | 2d+10e+8d+11e= | | 5/6x=-1/6 | | 3.1x+1=2.1x | | 3x+39=6x-9 | | 115-3x=24x+17 | | 115-5x=13x+21 | | 2x+8=778-5x | | 112-(9/5) | | x/2+12=-12 | | 9x+4y=5 | | 6=r+14 | | 3x+11=119-10x | | 8-10x=35-31x | | X-3n=5n | | 3x-3=3x^2-6x+3 | | 4(t-13)=9(t-3) | | 20-4y=4y-36 | | 5(t-5)=8(t+4) | | 3/5t+7=-8 | | 3(t+42)=7(t+126) | | 68-6x=39x+18 |